HISTORY OF THE DEVELOPMENT OF MADRASAH AS AN ISLAMIC EDUCATIONAL INSTITUTION - Luri Yutia Hadinda; Susanti, Novi; Yenni; Azis, Lasman; Iswandi, Iswandi; Soibatul Aslamiah Nasution (Amanah Publishing, 2026)
Education plays a crucial role in shaping individuals’ character and intellectual development, particularly within the context of Islamic education in Indonesia. Madrasahs, as Islamic educational institutions, have a long historical background and function as a bridge between religious instruction and general education. This study aims to examine the historical development of madrasahs, the educational patterns implemented within them, and their influence on the national education system in Indonesia. The research employs a descriptive qualitative approach, utilizing both primary and secondary data collected through relevant literature reviews, including books, scholarly articles, and academic journals. The findings indicate that madrasahs are not solely focused on teaching Islamic religious sciences but also integrate general knowledge into their curricula to respond to societal and educational demands. Furthermore, prominent figures such as KH. Hasyim Asy’ari and KH. Ahmad Dahlan played significant roles in reforming and developing madrasah education to remain relevant to the challenges of their time. The implications of this study highlight the importance of strengthening the madrasah education system as a means of building national character and contributing to the development of formal education in Indonesia. By enhancing the quality and structure of madrasahs, it is expected that future generations will emerge with strong academic competencies and good moral values, enabling them to face global challenges while maintaining Islamic principles.